2007
DOI: 10.1016/j.molonc.2007.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Identifying estrogen receptor target genes

Abstract: The estrogen receptor (ER) is a ligand inducible transcription factor that regulates a large number of target genes. These targets are particularly relevant in breast cancer, where the sensitivity of the tumor to estrogens determines whether the patients can be treated with endocrine therapy such as tamoxifen. Identifying genomic ER targets is a daunting task. Quantifying expression levels of suspected target genes after estradiol stimulation or, more recently, using expression microarrays to this effect will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 42 publications
2
48
0
Order By: Relevance
“…First, VDR/RXR binding occurs within introns and at distal intergenic sites greater than 95% of the time (5% promoter (Ϯ1 kb of the TSS), 60% intergenic, 30% introns, and 5% exon), an observation consistent with our earlier findings in cancer cells and with those for other nuclear receptors such as estrogen receptor and peroxisome proliferator-activated receptor ␥ as well (32,(37)(38)(39). Second, a de novo search for the most highly represented sequences found at sites bound by VDR or by both VDR and RXR in the two cistromes revealed the presence of a classic VDRE motif (Fig.…”
Section: Smoc2supporting
confidence: 90%
“…First, VDR/RXR binding occurs within introns and at distal intergenic sites greater than 95% of the time (5% promoter (Ϯ1 kb of the TSS), 60% intergenic, 30% introns, and 5% exon), an observation consistent with our earlier findings in cancer cells and with those for other nuclear receptors such as estrogen receptor and peroxisome proliferator-activated receptor ␥ as well (32,(37)(38)(39). Second, a de novo search for the most highly represented sequences found at sites bound by VDR or by both VDR and RXR in the two cistromes revealed the presence of a classic VDRE motif (Fig.…”
Section: Smoc2supporting
confidence: 90%
“…While a limited number of genes are known to be regulated by estrogen at present, recent evidence suggests that this list is likely much larger [2]. In lupus mouse models, studies have shown enhanced survival and decreased disease severity with ERα deficiency, while no effect was observed with regard to ERβ [3, 4]; thus supporting other studies also indicating the important role of the ERα receptor subtype in promoting autoimmune-mediated inflammation [5].…”
Section: Introductionmentioning
confidence: 68%
“…The phosphorylated and thus activated ERα regulates the transcription of target genes by protein-protein interaction with other transcription factors, such as SP1 (3,7,11). Many proteins encoded by these ERα-regulated genes are involved in regulating the cell cycle, angiogenesis, and survival (3,7,12,13).…”
mentioning
confidence: 99%